Global Warming and Loss of Bearing Capacity of Permafrost: An Experimental Study on the Effects of Freezing/Thawing Cycles on a Silty Soil - Howald, E. Prina; Torche, J. (Global Journal of Earth Science and Engineering, 2020)
One of the major effects of global warming is the thawing of permafrost. This phenomenon has several consequences on the affected environments, such as the loss of soil bearing capacity, the beginning of the seasonal cycles of freezing/thawing and an increase in the frequency of occurrence of natural hazards. This paper focuses on the loss of soil bearing capacity. A preliminary experimental study was carried out to understand and quantify the changes in the behaviour of a silty soil subjected to a freezing / thawing cycle through a series of laboratory tests. After the soil used for the lab tests was characterised, many shear tests and oedometric tests were performed before, during and after freezing. The geotechnical parameters were deduced from the oedometric curves and Mohr-Coulomb diagrams obtained. The comparison of the results made it possible to observe the evolution of the soil parameters, i.e. the internal friction angle, the cohesion, and the oedometric curves. All tests were carried out according to Swiss standards for laboratory testing